T26. VISUO-TACTILE TRANSFER AND AUDIO-VISUAL INTEGRATION IMPAIRMENT AS A NEW VULNERABILITY MARKER IN CHILDREN-AT-RISK OF SCHIZOPHRENIA, BIPOLAR DISORDER OR RECURRENT DEPRESSIVE DISORDER - Roy, Martin; Gilbert, Elsa; Maziade, Michel; Marquet, Pierre (Schizophrenia bulletin, 2020)
BackgroundMajor psychiatric disorders (MPD) such as schizophrenia, bipolar disorder and recurrent major depression have shared neurodevelopmental vulnerability due to early neuronal and sensory defect as revealed by sensory and cognitive endophenotypes observed in our cohorts (e.g. Gagné et al., Schizophr. Res., 2019). There is considerable evidence that a harmonious self-development - known to be disrupted in MPDs - requires a synchronized multisensory perception and an adequate integration of sensory afferences (e.g. tactile, visual, auditory and proprio / interoception) with cognition. Early impairment in intermodal transfer (IMT) and multisensory integration (MSI) may jeopardize a stable and unified self’s and world’s representation and then would undermine self-development and represent a risk factor for MPD. IMT is the capability to transfer a percept coming exclusively from a sensory modality (e.g. tactile) to another modality (e.g. visual). MSI is the ability to integrate sensory inputs from different modalities (e.g. visual and auditory) to have a better information processing. This study shows that impairment in IMT/MSI may be a vulnerability marker in children genetically at-risk.MethodsSample: Forty-four offspring (21 girls) of patients suffering from a MPD and thus genetically at-risk for MPD (GatR) aged from 9–15 years old (mean age = 12.06) were recruited from the cohort study INTERCEPT through the HoPE program of the CIUSSS de la Capitale-Nationale. Twenty-five controls (19 girls) with no family history of MPD and no DSM-V disorder aged from 9–15 years old (mean age = 12.87) were recruited using advertisements or control bank.IMT Task:Each condition has 12 trials and the shapes are hidden from sight during palpation.- T-T condition: The subject has to palpate a 3D target shape for 10s and must then recognize it by touch from among a distractor.- Condition T-V: The subject has to palpate a 3D target shape for 10s and must then recognize it visually from among a distractor.- V-T Condition: A 3D target shape is presented visually for 10s and the subject must then recognize it by touch from among a distractor.MSI Task: - Simple reaction time (RT) task comprising 80 trials with unimodal stimuli (Auditory OR Visual) and 40 trials with AV (Auditory and Visual simultaneously) multimodal stimuli presented randomly.- The Race model calculates the expected response probability for each RT knowing that AV RT could not be shorter than the shorter unimodal RT, if the sensory modalities are indeed separated channels (no MSI).- RTs shorter than those predicted by the Race model (best unimodal RT) are presumed to show multisensory facilitation which reflects MSI. The percentage of AV facilitation (AV – Race) is calculated for each reaction time.ResultsIMT task: When compared to controls, GatR were impaired in the three conditions (T-T: 9.77 vs. 10.32, T-V: 9.89 vs. 9.96, V-T: 9,11 vs. 9.92) with significant impairments both for T-T (t(60.53) = 2.18, p = 0.017) and V-T (t (57.28) = 2.33, p = 0.012) conditions.MSI task: GatR showed a deficit in MSI for almost all RT ranges (except for a peak at 185 ms), while control participants showed MSI facilitation for ranges from 150 to 200 ms.DiscussionDevelopmentally genetically high-risk children would show significant impairments both in IMT and MSI that might enter into the group of indicators of brain dysfunctions, or risk endophenotypes, that both children at risk and adult patients carry (Paccalet et al., Schizophr. Res., 2016; Maziade, New Eng J Medicine, 2017). In addition, the two tasks would be valid and sensitive to the early sensory alterations in self-development. Finally, the battery is brief, user-friendly and playful for children.